2013
DOI: 10.1080/13825585.2013.824064
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the distractor previewing effect with schematic faces of emotions

Abstract: Young and older adults searched for a unique face in a set of three schematic faces and identified a secondary feature of the target. The faces could be negative, positive, or neutral. Young adults were slower and less accurate in searching for a negative face among neutral faces when they had previewed a display of negative faces than when they had previewed neutral faces, indicating an emotional distractor previewing effect (DPE), but this effect was eliminated with inverted faces. The DPE is an index of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Overall, the research shows support for the NST [20,22] in that common names show superior recall, encoding, consolidation, and retrieval/retention over uncommon names. In further support of the FNAT, when controlling for the age [68] and emotional expressions of the to-be-remembered faces [69] , older adults show a deficit across all EM variables for recalling names in association with unknown faces.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Overall, the research shows support for the NST [20,22] in that common names show superior recall, encoding, consolidation, and retrieval/retention over uncommon names. In further support of the FNAT, when controlling for the age [68] and emotional expressions of the to-be-remembered faces [69] , older adults show a deficit across all EM variables for recalling names in association with unknown faces.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have suggested that younger and older participants respond differently to faces with different emotional expressions [69] , ages [68] , and celebrity status [66] . Hence, experiment 1 used computer-generated faces of older adults with neutral expressions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations